Penerapan Metode Profile Matching Pada Sistem Pendukung Keputusan Pemilihan Ketua Program Studi (STUDI Kasus : Program Studi Teknik Informatika STMIK Musi Rawas) - Andri Anto Tri Susilo (JUITA : Jurnal Informatika, 2017)
Abstract-- In the organizational structure of a study program, always led by a chairman of the study program. In STMIK Musi Rawas, the process of selecting the head of the study program is usually appointed directly by the chairman of the foundation. The shortcomings of the direct appointment process is not able to see the capabilities possessed by the candidate chairman of the study program be it social skills, planning, management of learning, management of Human Resources, Finance and so forth. Decision support system is a system that can be used to help make decisions based on existing criteria. In this research the method used is Profile Matching method. The concept of Profile Matching method is to compare individual competence into job competence so that it can know the difference of competence (also called gap), the smaller the gap that is generated, the greater the value the greater the greater the chance for someone to occupy the position. The end result of this research is obtained information about the highest value of each candidate chairman of the Study Program based on the calculation of Profile Matching